Fixed Point Theorems for \((ξ,α)\)-Expansive Mappings in Metric Like Spaces - Kumar, Manoj; Kumari, Nisha (Communications in Mathematics and Applications, 2024)
In this paper, we shall introduce the \((ξ ,α )\)-expansive mappings and prove some fixed point theorems for these mappings in complete metric like spaces. We shall also provide examples to illustrate the main results.